Learning Strategies at SD Muhammadiyah 1 Sedati during the Covid 19 Pandemic - Devina Regita Cahyarani; Muhlasin Amrullah (International Consortium of Education and Culture Research Studies, 2021)
This research is motivated because there are many changes to the world caused by a virus that is currently rife, namely the corona virus or we can call it Covid-19. Likewise in Indonesia, the existence of this virus encourages people to stay at home during the Covid-19 pandemic, the serious impact of which affects various sectors. One of them is in the field of education, which requires students to study at home. And teachers also teach from home with online methods, through various sophisticated applications today, as technology and information advances. This is because face-to-face learning is not allowed to avoid crowds as an effort to break the chain of virus spread. The purpose of this study was to determine the learning strategies used by SD Muhammadiyah 1 Sedati during the Covid-19 pandemic. And how from the school regarding the school's flagship program and instilling the character of Muhammadiyah in students so that it continues to run during this Covid-19 period. In the process of this research using data collection methods with interviews, observation and documentation. The results showed that the strategy used by SD Muhammadiyah 1 Sedati was using mixed learning methods, where learning was carried out online or in a network and face-to-face with procedures determined by the school by applying health protocol rules. Based on the research that has been done, it can be concluded that the presence of Covid-19 makes people pay more attention to cleanliness and health by implementing health protocols. As well as making advanced technology such as digital media increasingly developing, due to innovations to find the best solutions for learning during the Covid-19 pandemic.